2021
DOI: 10.1021/acs.inorgchem.0c03742
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Geometry Changes in Amorphous Cyanide-Bridged Metal–Organic Frameworks upon Water Adsorption

Abstract: Amorphous coordination polymers and metal–organic frameworks (MOFs) have attracted much attention owing to their various functionalities. Here, we demonstrate the tunable water adsorption behavior of a series of amorphous cyanide-bridged MOFs with different metals (M­[Ni­(CN)4]: MNi; M = Mn, Fe, and Co). All three compounds adsorb up to six water molecules at a certain vapor pressure (P ads) and undergo conversion to crystalline Hofmann-type MOFs, M­(H2O)2[Ni­(CN)4]·4H2O (MNi–H 2 O; M = Mn, Fe, and Co). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 60 publications
(81 reference statements)
4
24
0
Order By: Relevance
“…Next, we present the L 2,3 -edge XAS spectra of MnNi, FeNi, and CoNi. As in previous XAS studies by Yoshino et al, 20 the asymmetric Mn, Fe, and Co L 2,3 -edge XAS spectra were clearly observed by scanning the hn from 630 to 665 eV, 690 to 740 eV, and 755 to 830 eV, respectively (Fig. 3(a-c)).…”
Section: Xas Spectra Of Mnni Feni and Conisupporting
confidence: 83%
See 3 more Smart Citations
“…Next, we present the L 2,3 -edge XAS spectra of MnNi, FeNi, and CoNi. As in previous XAS studies by Yoshino et al, 20 the asymmetric Mn, Fe, and Co L 2,3 -edge XAS spectra were clearly observed by scanning the hn from 630 to 665 eV, 690 to 740 eV, and 755 to 830 eV, respectively (Fig. 3(a-c)).…”
Section: Xas Spectra Of Mnni Feni and Conisupporting
confidence: 83%
“…which differentiates it from a previous study 20 and adds to the previous results in a complementary manner. Further details can be found in the ESI.…”
Section: Xas Spectra Of Mnni Feni and Conisupporting
confidence: 73%
See 2 more Smart Citations
“…S7 †). 37,38 Only the broadness of the nCN bands is observed in AgCu-g and AgAu-g with a negligible shi (Fig. S8 and S9 †).…”
Section: Structural Characterization Of Migsmentioning
confidence: 99%